2016
DOI: 10.1080/13678868.2016.1248720
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate contact with a local host: an intervention to increase social support

Abstract: Social capital is a crucial factor for expatriates to employ as they cope with the demands of an international assignment. This longitudinal study used a mixed method approach to examine the social support benefits of expatriate contact with a local host. Western expatriates in the Netherlands were randomly divided into two groups: an experimental group (n = 33), that had contact with a Dutch host during 9 months, and a control group (n = 32) with no host. Qualitative methods such as interviews and diaries wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 63 publications
(96 reference statements)
2
54
0
Order By: Relevance
“…Furthermore, some of the perceived challenges are particular to the sports expatriate population. While every expatriate has to build a new social network when moving abroad (van Bakel, van Oudenhoven, & Gerritsen, ), it might be more difficult for sports expatriates to build a new social network outside of their immediate work environment due to their time schedule; they often have practice when others are off work, and have to play games in the weekend. Future research should examine in more detail how sports expatriates can build new social networks when abroad, since social support has been found vital for expatriate adjustment (Wang & Kanungo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the perceived challenges are particular to the sports expatriate population. While every expatriate has to build a new social network when moving abroad (van Bakel, van Oudenhoven, & Gerritsen, ), it might be more difficult for sports expatriates to build a new social network outside of their immediate work environment due to their time schedule; they often have practice when others are off work, and have to play games in the weekend. Future research should examine in more detail how sports expatriates can build new social networks when abroad, since social support has been found vital for expatriate adjustment (Wang & Kanungo, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study advances international business research by contributing to global migration and international careers research, which have been identified as key areas for investigation by international business scholars (Caligiuri and Bonache, 2016;Doh, 2015aDoh, , 2015bDoh, , 2017. In particular, this study contributes to literatures on newcomers' adjustment and labour market integration (e.g., Farh et al, 2010;Guo and Al Ariss, 2015;Sidani and Al Ariss, 2014;Sambasivan et al, 2017;Tung, 2016), newcomers' adjustment and online technology use (e.g., Mikal et al, 2013Mikal et al, , 2015Nardon et al, 2015), and newcomers and social support (e.g., Podsiadlowski et al, 2013;Stroppa and Spieß, 2011;Van Bakel et al, 2017) by showing that online discussion forums facilitate exchange of social support online, which can help newcomers with adjustment and integration in the new country's labour market.…”
Section: Canadian Immigrationmentioning
confidence: 59%
“…The various information sources can be grouped into four main categories: social networks (e.g., friends and family), formal sources (e.g., government organizations), media (e.g., ethnic television), and information and communication technologies (e.g., the Internet) (Caidi et al, , 2010Podsiadlowski et al, 2013;Van Bakel et al, 2017). The following sections discuss each of the four categories in more details.…”
Section: Information Sources Of Newcomersmentioning
confidence: 99%
See 2 more Smart Citations